2009
DOI: 10.1016/j.neubiorev.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Atypical eye contact in autism: Models, mechanisms and development

Abstract: An atypical pattern of eye contact behaviour is one of the most significant symptoms of Autism Spectrum Disorder (ASD). Recent empirical advances have revealed the developmental, cognitive and neural basis of atypical eye contact behaviour in ASD. We review different models and advance a new 'fast-track modulator model'. Specifically, we propose that atypical eye contact processing in ASD originates in the lack of influence from a subcortical face and eye contact detection route, which is hypothesized to modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
333
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(371 citation statements)
references
References 135 publications
18
333
1
3
Order By: Relevance
“…However, we provide the first eye tracking evidence of reduced face gaze during real interaction, contrasting with the findings of Nadig et al (2010). Importantly, we also provide evidence of attention to face regions and indicate that not only is face gaze reduced in autism, but attention to the eyes of the interlocutor is most atypical, which has theoretical significance (Klin & Jones, 2008;Pruett et al, 2011;Senju & Johnson, 2009). This supports previous screen-viewing eye-tracking studies (Hanley et al, 2012;Klin et al, 2002b).…”
Section: Attention To the Face During Real Interactionsupporting
confidence: 46%
“…However, we provide the first eye tracking evidence of reduced face gaze during real interaction, contrasting with the findings of Nadig et al (2010). Importantly, we also provide evidence of attention to face regions and indicate that not only is face gaze reduced in autism, but attention to the eyes of the interlocutor is most atypical, which has theoretical significance (Klin & Jones, 2008;Pruett et al, 2011;Senju & Johnson, 2009). This supports previous screen-viewing eye-tracking studies (Hanley et al, 2012;Klin et al, 2002b).…”
Section: Attention To the Face During Real Interactionsupporting
confidence: 46%
“…For example, there is growing interest in the study of autism, a developmental condition characterised primarily by impairments in social and communication skills, as a model for the development of the 'social brain' Senju & Johnson, 2009). In typical adults, regions such as the orbitofrontal cortex, the amygdala, temporal lobe face-sensitive regions, temporo-parietal junction, and the superior temporal sulcus (STS) are among those primarily involved in the processing of socially-relevant information (Adolphs, 2003).…”
Section: Modelling Interactions In the Developing Brainmentioning
confidence: 99%
“…These claims are based on the large number of studies documenting reduced attention to faces (Hutt and Ounsted 1966;Trepagnier et al 2002;Riby and Hancock 2008;Sasson et al 2007;Bal et al 2010;Baranek 1999;Chawarska and Shic 2009;Osterling and Dawson 1994;Osterling et al 2002;Hernandez et al 2009) and/or atypical eye fixation in autism (as initially detailed in Kanner's first descriptions of autism, Kanner 1943Kanner , 1944; see also Joseph and Tanaka 2003;Riby and Hancock 2008;Boraston et al 2008;Sterling et al 2008;Jones et al 2008; for a review see Senju and Johnson 2009a). Klin et al (2002) assessed fixation patterns while participants observed emotional movie clips containing social interaction.…”
mentioning
confidence: 99%
“…Despite the abundance of studies demonstrating atypical face and eye fixation in autism, an equally large number of studies have found contradictory results; showing no evidence for reduced fixations on the face and/or altered eye or mouth fixations in children or adults with autism (O'Connor and Hermelin 1967; Dapretto et al 2006;Neumann et al 2006;Rutherford and Towns 2008;Lahaie et al 2006;Falck-Ytter et al 2010;Freeth et al 2010;Fletcher-Watson et al 2009; see Senju and Johnson 2009a for an overview). Young et al (2009) studied the gaze behaviour of 6 month-old infants, some of which were considered at-risk for autism due to having affected siblings.…”
mentioning
confidence: 99%